Localized molecular orbitals for calculation and analysis of vibrational Raman optical activity. Issue 45 (9th November 2018) - Luber, Sandra
Abstract : First calculations of vibrational Raman optical activity based on localized molecular orbitals are presented, which pave the way for novel insight into spectroscopic signatures of chiral systems. Abstract : We present a novel method for the calculation of vibrational Raman optical activity (ROA) spectra based on localized molecular orbitals. This allows to split total ROA intensities into contributions of subsets, which can be chosen flexibly depending on the question of interest. It provides an appealing way to gain deeper insight into the factors influencing chirality and associated bands observed in the spectrum. As example, the ROA spectrum of a tryptophan model system, in particular the band arising from its W3 vibration, has been investigated.